Nicolaides-Baraitser syndrome in the assessment of an interdisciplinary team - Michalska, Agata; Wendorff, Janusz; Uranowska, Mariola; Linowski, Michał; Baran, Aleksandra; Szawracka, Agnieszka (Medical Studies/Studia Medyczne, 2013)
Nicolaides-Baraitser syndrome (NBS) is a rare entity (26 cases in the world, one in Poland) of an unknown aetiology. It is characterised by a profound intellectual disability, limited or no active speech and the presence of epilepsy. From a phenotype perspective, NBS manifests itself in short height, thinning hair, a characteristic shape of the face, brachydactyly, enlarged interphalangeal joints of fingers and wide distal phalanges. The authors present a case of a patient with NBS who is presently 25 years old, assessing her current state of health along with all spheres of development.